2013
DOI: 10.1073/pnas.1214046110
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of circulating microRNA via small RNA sequencing of cDNA libraries reveals biomarker potential and limitations

Abstract: We profiled microRNAs (miRNAs) in cell-free serum and plasma samples from human volunteers using deep sequencing of barcoded small RNA cDNA libraries. By introducing calibrator synthetic oligonucleotides during library preparation, we were able to calculate the total as well as specific concentrations of circulating miRNA. Studying trios of samples from newborn babies and their parents we detected placental-specific miRNA in both maternal and newborn circulations and quantitated the relative contribution of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
268
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 319 publications
(291 citation statements)
references
References 49 publications
13
268
2
4
Order By: Relevance
“…We used a small RNA-sequencing (sRNAseq) protocol developed for parallel processing of large sample collections with limited amounts of input RNA (7,34,35) to record the miRNA composition in heart tissue and in circulation in a large cohort of HF patients and normal controls. Using the same method for miRNA profiling eliminated biases (26) otherwise affecting comparison of our data with studies, which previously profiled either tissue or circulating miRNAs in HF, but never both.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a small RNA-sequencing (sRNAseq) protocol developed for parallel processing of large sample collections with limited amounts of input RNA (7,34,35) to record the miRNA composition in heart tissue and in circulation in a large cohort of HF patients and normal controls. Using the same method for miRNA profiling eliminated biases (26) otherwise affecting comparison of our data with studies, which previously profiled either tissue or circulating miRNAs in HF, but never both.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with siRNAs or antagomirs (29) showed that only highly expressed miRNAs effectively repress target mRNAs. For simplicity of data presentation and discussion, we thus focused on regulatory miRNAs that contribute to ∼85% of sequencing reads per sample (7,25), corresponding to 15, 25, 21, and 28 miRNA cistrons in NFs, FETs, DCM HF, and ICM HF, respectively ( Fig. 2 A-C and Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…92 It is difficult to determine what is the minimal amount of miRNA that is sufficient for biological activity, and whether such an amount can be efficiently delivered to the host via e.g., the gastrointestinal tract. It has been suggested that miRNA copy number of about one hundred to one thousand per cell would be needed to affect gene expression.…”
Section: Required Amount Of Mirnas For Biological Activitymentioning
confidence: 99%
“…In contrast with cancer immunosurveillance that is a rather slow process, such miRNA-mediated tumor suppressing activity could be very rapid and thus might complement the immune activity for tumor prevention. This is certainly a hypothesis and major counter arguments could be deployed against it including the very low concentration of individual miRNA in the circulation (femtomolar range), 92 the dual nature of miRNA (the same miRNA can be oncogenic in one, and tumor suppressor in another tissue), their tissue specificity etc. 105 By extending this hypothesis, it cannot be excluded that absorbed exogenous miRNA might interfere with tumor formation, as well.…”
Section: Hypotheses Relating Xeno-mirna and Diseasesmentioning
confidence: 99%